Morally “loaded” labels in the built environment influence perceptions and social judgments - Haga, Andreas (Frontiers in Psychology, 2024)
Products and artifacts with morally loaded labels (e.g., environmentally friendly) appear to change people’s perceptions and behavior. Previous studies have shown that desktop lamps labeled “environmentally friendly” can enhance perceived color discrimination and certain reading activities, compared to a physically identical lamp labeled “conventional”. This phenomenon might arise because people may behave in line with moral principles. The generalizability and robustness of this label effect was explored in the present study, by asking participants to make trait judgments of photographed faces. In an experimental design, participants judged photos enlightened by a desktop lamp that was either labeled environmentally friendly or not labeled at all. The results revealed that participants assigned more positive traits to the photographed persons when the lamp was labeled “environmentally friendly”, at least those with high altruistic values. The pattern was reversed for people with low altruistic values. Moreover, participants rated the light from the lamp labeled “environmentally friendly” as more comfortable and claimed that the light increased (perceived) visibility. In conclusion, the source (an environmentally friendly or a conventional lamp) from which the light originates changes the evaluation of the light itself and judgments of other individuals. The paper discusses theoretical explanations of the label effects as well as its implications for pro-environmental interventions.